2017
DOI: 10.1016/j.healun.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage/monocyte-specific deletion of Ras homolog gene family member A (RhoA) downregulates fractalkine receptor and inhibits chronic rejection of mouse cardiac allografts

Abstract: Background The cellular and molecular mechanisms of chronic rejection of transplanted organs remain obscure. It is known however that macrophages play a critical role in the injury and repair of allografts. Among multiple factors influencing macrophage infiltration to allografts, the fractalkine CX3CL1/ CX3CR1 signaling pathway and actin cytoskeleton, which is regulated by a small GTPase RhoA, are of the utmost importance. To define the role of macrophage/RhoA pathway involvement in chronic rejection we genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…M0 macrophages are naive/unpolarized macrophages. Two of the most common subtypes of activated macrophages are M1 proinflammatory ''killer'' macrophages, which produce damaging reactiveoxygen species and express the nitric oxide synthase iNOS, and M2 antiinflammatory ''repair'' macrophages, which produce the enzyme arginase-1 that depletes L-arginine and deprives iNOS of its substrate (1)(2)(3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…M0 macrophages are naive/unpolarized macrophages. Two of the most common subtypes of activated macrophages are M1 proinflammatory ''killer'' macrophages, which produce damaging reactiveoxygen species and express the nitric oxide synthase iNOS, and M2 antiinflammatory ''repair'' macrophages, which produce the enzyme arginase-1 that depletes L-arginine and deprives iNOS of its substrate (1)(2)(3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the liver injury mouse model showed that the CCR2 knockout causes impairment in the recruitment of monocytes and collagen production/injury‐related fibrosis (Seki et al, ). Studies from our laboratory showed that the macrophage specific knockout of small GTPase RhoA inhibited expression and recycling of CX3CR1 receptors in the macrophages, which in turn prevented their movement to the transplanted heart and inhibited chronic rejection in mouse transplantation model (Liu, Chen, et al, ). These findings suggest that targeting of CX3CR1/fractalkine via RhoA pathway inhibition may be also useful for the manipulation of macrophage recruitment into the wound site.…”
Section: Monocytes and Macrophagesmentioning
confidence: 99%
“…We showed that macrophage‐specific deletion of RhoA, inhibition of ROCK or inhibition of RhoA activator GEFs (Chen, Li, Kubiak, Ghobrial, & Kloc, ), elongates macrophages (they switch into M2 prohealing phenotype), disrupts their Golgi complex and receptor recycling pathway, and influences extracellular matrix degradation. All these changes prevented macrophages from entering the transplanted hearts and inhibited chronic (long term) rejection (Chen, Chen, Chen, et al, ; Chen, Ghobrial, Li, & Kloc, ; Chen, Sandoval, et al, ; Liu, Chen, et al, ; Liu, Kloc, & Li, ; Liu, Minze, et al, ; Liu, Tejpal, et al, ; Liu, Chen, et al, ; Liu, Kubiak, Li, Ghobrial, & Kloc, ; Wu et al, ). We also showed that interference with the RhoA pathway disrupted recycling and expression of CX3CR1 (fractalkine) receptor in monocytes and macrophages and prevented their movement into the graft (Figure ; Liu, Chen, et al, ).…”
Section: Molecular Mechanisms Of Macrophage Polarisation and Cytoskelmentioning
confidence: 99%
See 2 more Smart Citations